How we raise our daughters and sons child-rearing and gender socialization in the Philippines - Liwag, Ma. Emma Concepcion; de la Cruz, Alma S.; Macapagal, Ma. Elizabeth J. (Philippine Journal of Psychology, 1998)
The literature on Filipino child-rearing practices as they relate to gender socialization was surveyed in order to describe child-rearing attitudes, beliefs, expectations, and practices from early childhood to late adolescence which demonstrate explicit and implicit differential socialization for sons and daughters. Findings from more than a hundred empirical and conceptual papers on Filipino child-rearing indicated that specific expectations of masculine and feminine behaviors were mirrored in the family in six socialization areas, including 1) parental preferences for children of one gender or another; 2) what parents expect of their daughters in contrast to what they expect of their sons, and consequently; 3) how parents raise their daughters in contrast to how they raise their sons; 4) how families invest their resources unequally upon daughters and sons; 5) the types of differential responsibility training given to daughters and sons; and 6) parental modeling as indicated by differences in the child-rearing behaviors of mothers and fathers. The review affirmed the role of the family as the major site of gender socialization of Filipino children.